LABA AKUNTANSI DAN KLASIFIKASI AKUNTANSI UNTUK MENAKSIR PROFITABILITAS PERUSAHAAN - PRIHAT ASSIH (Jurnal Bisnis dan Akuntansi, 1999)
Earnings have information content to predict two benefits of equity investment earnings and cash flow from operation. And disaggregation earnings or net income into spesific components that the accounting profession's requires is important for assessing firm profitability. This study examine the predictive content of earnings and earnings disaggregations. The results demonstrate that earnings are a significant predictor of future earnings but does not a significant predictor of future cash flow, and does not support that earnings disaggregation improves profitability forecasts.